2015
DOI: 10.4103/0971-5916.162093
|View full text |Cite|
|
Sign up to set email alerts
|

Drug-induced diseases (DIDs): An experience of a tertiary care teaching hospital from India

Abstract: Background & objectives:Drug-induced diseases (DIDs) are well known but least studied. Data on DIDs from India are not available. Hence, this retrospective cross-sectional study was undertaken using suspected adverse drug reaction (ADR) data collected form Pharmacovigilance Programme of India (PvPI) to evaluate profile of DIDs over two years, in a tertiary care teaching hospital from north India.Methods:The suspected ADRs in the form of DID were evaluated for drug and disease related variables and were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
3
12
1
3
Order By: Relevance
“…Likewise a prospective study from Portugal reported that 22.9 per cent of patients admitted in the department of internal medicine developed iatrogenic disease 5 . In the present study by Tandon and colleagues 1 , the reported incidence of DID is 38.8 per cent. However, contrary to previous studies, the present study was retrospective and the data were obtained from the ADRs reported to Adverse Drug Reaction Monitoring Center, functioning under PvPI.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Likewise a prospective study from Portugal reported that 22.9 per cent of patients admitted in the department of internal medicine developed iatrogenic disease 5 . In the present study by Tandon and colleagues 1 , the reported incidence of DID is 38.8 per cent. However, contrary to previous studies, the present study was retrospective and the data were obtained from the ADRs reported to Adverse Drug Reaction Monitoring Center, functioning under PvPI.…”
supporting
confidence: 49%
“…The true incidence or prevalence of DID in our country is not known. The results of the study by Tandon et al 1 in this issue provide information on DID in Indian setting. Although the study has a few limitations and overlap between adverse drug reactions (ADR) and DID, yet it flags an important issue which needs attention.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However, these were not considered further due to lack of any systematic investigation into causes or frequency of occurrence. Similarly, several studies and systematic reviews evaluated the occurrence of ADRs among people receiving pharmacotherapy in hospitals and/or in community settings (Geer et al, 2016;Tandon et al, 2015;Hiware et al, 2013;Patel and Patel, 2016;Patel et al, 2014;Patel et al, 2013). Although antimicrobials were often found to be a major contributor to adverse reactions experienced by patients, these studies were not included since their primary focus was not on antimicrobial safety.…”
Section: Safetymentioning
confidence: 99%
“…The amount of prescription data available to clinical researchers, pharmaceutical scientists, and clinician-scientists continues to grow, creating an analyzable resource for generating insights that can help improve the healthcare system [4,5]. Healthcare providers use modern EMR-based systems to identify adverse drug events [6,7], study medication-medication interactions [8], investigate medication effects on particular medical conditions [9,10], and ultimately prevent medication errors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%